A novel treatment for glioblastoma: integrin inhibition. (April 2012) - Chamberlain, Marc C; Cloughsey, Timothy; Reardon, David A; Wen, Patrick Y
Glioblastoma (GBM) is the most common malignant primary brain tumor, which despite combined modality treatment, recurs and is invariably fatal. New therapies for GBM represent an unmet need in neuro-oncology. This review provides an overview of the epidemiology and molecular biology of GBM and focuses, in particular, on integrins, which are heterodimeric transmembrane surface proteins that, when activated, signal through several GBM-relevant pathways, including proliferation, motility, cytoskeleton organization, survival and angiogenesis pathways. Consequently, the potential effects of anti-integrin strategies in anti-GBM therapeutics are threefold: antiangiogenesis; anti-invasion; and anti-tumor. Trials of anti-integrins are most mature in GBM, and this review summarizes the completed and future trials of integrin inhibitors in the treatment of both newly diagnosed and recurrent GBM.